Madrasah-Oriented Educational Management - Husein Yusuf, Muhammad; Fatima, Aulia; Patimah, Hj. Siti (Jurnal Multidisiplin Indonesia, 2023)
The importance of madrasa-centered management and issues related to the management of the curriculum in madrasah in order to facilitate the learning process in an educational institution. This article aims to understand the concepts of Islamic education management, curriculum management, student affairs, infrastructure, finance, and the challenges Madrasah management faces. This article is written based on a literature study. This study relies on library research methods, where the necessary data and information to refine this article are taken from sources available in libraries, such as books and journals. A description of the madrasah, including its issues, curriculum management, facilities and infrastructure management, student management, financial management, and management challenges. Management is crucial in ensuring the smoothness of the learning process at educational institutions, including establishing positive relationships between the institution and parents or students, as well as the community. This discussion will address aspects of management at educational institutions, such as Madrasah management and its issues, curriculum management, facilities and infrastructure management, student management, and financial management and its challenges. All elements within the management of educational institutions must be integrated and have a close reciprocal relationship because if one aspect encounters problems, the learning process can be disrupted.